Research and development of approaches for the analysis of the current pricing system of project work - Shumak, L. (Ways to Improve Construction Efficiency, 2023)
At the current stage of the transition period associated with military actions in the economy of Ukraine, the issue of pricing for design and scientific-project work in the construction industry is the most acute and the most relevant. The perception of price is increasingly associated with the designations fixed by this concept, such as "state", "market", "enterprise", "contract". The meaning of the price, however, is related to the price-forming factors that affect its value. In the conditions of market relations, the labor, material and financial resources of the project enterprise are part of the aggregate resources of society and are included in the general reproductive process by the project enterprise itself as a business entity. The regulation of reproduction occurs in combination with other economic and value laws acting through price mechanisms and pricing. Pricing policy and price management play an important role in the life of project enterprises - one of the main points in the strategic development of project enterprises. In order to form a high-quality price policy, project enterprises need to collect information about the market, conduct research, prepare and propose new projects, and optimize sales of project products. On the basis of the analysis of the collected information about the project market, the project enterprises form a price policy. The article analyzes the available literature on design, construction, operation, monitoring, in particular, on determining the cost of design and scientific project works. The article contains the results of a literature review devoted to issues of pricing in design. Currently, there are no Designer’s Guides available for costing design and engineering work, requiring practicing engineers and public universities to rely on experience and private service. The article proposes scientific developments in the direction of improving the pricing of project works, which require, first of all, the study of clear trends and hidden regularities of the influence of a number of factors. An approach to determining the cost of design works is recommended, primarily taking into account the physical parameters of the design object and the economic factors of its construction. It is proposed to study the interrelationships between these factors: – using statistical data analysis methods; - means of artificial intelligence. In the course of the study, an in-depth analysis of the cost of design works was carried out for objects under construction in the city of Kyiv and the Kyiv region. The analysis of the cost of design works was carried out from individual elements of the structure. The main part of the scientific research of the article on the determination of the cost of project works is devoted to the study of the problem of pricing and the development of approaches for the analysis of the current system of pricing of project works in Ukraine.